Comparative institutional analysis of participation in collaborative learning - Eisuke Saito; Thi Diem Hang Khong; Yasunobu Sumikawa; Miki Watanabe; Arif Hidayat (Cogent Education, 2020)
Recently, group learning has been introduced in various countries as part of educational reform. While there are various approaches to group learning, the focus of this study is on collaborative learning, which is based on mutual help-seeking and consultation. This requires teachers’ decision to integrate collaborative learning into their practices and all actors to participate therein. This demonstrates whether implementing and participating in collaborative learning is a game theoretic situation. However, in the majority of studies on group learning, the game theoretic aspect has not been sufficiently investigated. Therefore, this paper aims to provide a conceptual discussion on this situation in collaborative learning using a comparative institutional analysis (CIA) framework.